The conservation of native priority medicinal plants in a Caatinga area in Ceará, northeastern Brazil - SANTOS, MARIA O.; ALMEIDA, BIANCA V. DE; RIBEIRO, DAIANY A.; MACÊDO, DELMACIA G. DE; MACÊDO, MÁRCIA J.F.; MACEDO, JULIMERY G.F.; SOUSA, FRANCISCA F.S. DE; OLIVEIRA, LIANA G.S. DE; SARAIVA, MANUELE E.; ARAÚJO, THATIANE M.S.; SOUZA, MARTA M.A. (Anais da Academia Brasileira de Ciências, 2017)
Much of the Brazilian semiarid region faces a considerable process of degradation of natural resources, and ethnobotanical studies have collaborated with important information about the use and traditional knowledge, serving as a tool to design conservation strategies of native plant species. Thus, this study aimed to determine medicinal species meriting conservation priorities in a "Caatinga" area in the northeastern of Brazilian territory. The ethnobotanical data were collected through semi-structured interviews with key subjects selected through the "snowball" technique. The availability and species conservation priority was verified by relative density, risk of collection, local use and use of diversity in the forest fragment sampled. It was recorded 42 native medicinal plants and conservation priority score was calculated for seven species, including Mimosa tenuiflora, Hymenaea courbaril, Ximenia americana and Amburana cearensis need immediate conservation and attention, since their collection does not occur in a sustainable way. In order to ensure the perpetuation of the species and the sustainability of traditional therapeutic practice there needs to be a development of conservation practices of caatinga remaining to better conserve the species of the biome.